Salsa : un poema para cocinar - Argueta, Jorge (Groundwood Books / House of Anansi Press, 2015)
In this new cooking poem, Jorge Argueta brings us a fun and easy recipe for a yummy salsa. A young boy and his sister gather the ingredients and grind them up in a molcajete, just like their ancestors used to do, singing and dancing all the while.